Development of a Chlamydia suis‐specific antibody enzyme‐linked immunosorbent assay based on the use of a B‐cell epitope of the polymorphic membrane protein C. Issue 2 (4th January 2018) - De Puysseleyr, K.; Kieckens, E.; De Puysseleyr, L.; Van den Wyngaert, H.; Ahmed, B.; Van Lent, S.; Creasy, H. H.; Myers, G. S. A.; Vanrompay, D.
Summary: Chlamydia suis infections lead to economic loss in the pork industry. Chlamydia suis infections could be successfully treated with tetracyclines until the appearance of a tetracycline resistant phenotype, which was acquired via horizontal gene transfer of the tet (C) gene. Given the importance of C. suis as a swine pathogen and as a recently emerged tetracycline resistant pathogen with zoonotic potential, our aim was to develop a sensitive C. suis ‐specific antibody ELISA based on the polymorphic membrane proteins (Pmps). Chlamydia Pmps are important virulence factors and candidate antigens for serodiagnosis. We identified nine Pmps (PmpA to I) in C. suis strain MD56 using a recently developed Hidden‐Markov model. PmpC was the most promising candidate for the development of a C. suis ‐specific antibody ELISA as the protein was absent in C. abortus, C. pecorum and C. psittaci which also infect pigs and as the protein contained C. suis ‐specific amino acid regions, absent in C. trachomatis PmpC. We identified an immunodominant B‐cell epitope in C. suis PmpC using experimental porcine sera. The sensitivity and specificity of the PmpC ELISA was compared to the complement fixation test (CFT) and to a recombinant MOMP ELISA using experimental sera. The PmpC ELISA detected all positive control sera and was in contrast to CFT and the rMOMP ELISA 100% C. suis specific as positive control sera against other Chlamydia species did not react in the PmpC ELISA. The test was successfully validated using slaughterhouse sera and sera from clinically affected pigs. The PmpC ELISA could assist in diminishing the spread of C. suis infections in the pork industry.